The Concept of the Sharing Economy from an Islamic Economic Perspective - Tobroni, M.Kamil; Bte Badrul Munir , Maryam; Hilmi, Ahmad (Journal Creative Economics and Trading Halal Ecosystem, 2024)
The sharing economy has emerged as a worldwide phenomenon, transforming consumption and production patterns within society. This approach relies on the collective use of resources via digital channels. From the standpoint of Islamic economics, the sharing economy is significantly pertinent to ideals such as justice, integrity, and communal welfare. This article examines the sharing economy within the framework of Islamic economics, assesses its adherence to sharia principles, and analyzes its advantages and obstacles